The role of foster carers in England and Portugal: Is it solely a parenting role?. (9th January 2022) - Pinto, Vânia S.; Luke, Nikki
Abstract: The role of foster carers can be described as similar to the role of parents, but with some additional tasks. Through focus groups, children in care, young adults who are care‐experienced, foster carers, and social workers in England and Portugal shared their views on this role. Key themes included the need to promote children's sense of belonging and relationships with foster carers and their birth family, to support children's individual needs, and to recognise the influence of children's social care services, social workers and foster carers' family and social network. Foster carers and social workers in the English sample talked about the complementarity between the parenting side of the role and these additional tasks. On the other hand, children and young adults in both samples, and foster carers and social workers in the Portuguese sample, focused mostly on the parenting side of the role, but also stated the importance of some additional tasks, such as collaboration with children's birth families. These findings reflect policies and alternative care context differences between England and Portugal.